The Visage of a Dream: Culture, Commodity and Affect in Rosalia de Castro's El caballero de las botas azules (1867). Issue 5 (1st May 2022) - O'DWYER, MANUS
Abstract : Critics of the work of Rosalía de Castro (1837–1855) have noted the difficulties her novel El caballero de las botas azules (1867) poses for both Spanish and Galician literary historiography. A metafictional satire written in Spanish and set in Madrid, it is difficult to place within narratives of Galician literary history that imagine Rosalía as a saintly founding mother, as well as within narratives of Spanish literary history that imagine a teleological development of the novel from Romantic to Realist forms. This article will situate El caballero as a hinge text, a farewell to a Romantic poetics of melodrama and named emotions and a move towards a modern literature of affect, a transition that is inflected by a profound meditation on the role of literature within a world of increasing consumerism and commodification. The discussion will be framed in terms of the twin themes of hysteria and dandyism.